Compression behaviors of 3D printed pyramidal lattice truss composite structures. (1st February 2020) - Ye, Gaoyuan; Bi, Hongjie; Hu, Yingcheng
Abstract: The lattice truss structure is a porous lightweight periodic structure with high specific stiffness and specific strength. In this research, pyramid lattice truss structures were designed and manufactured by three-dimensional (3D) printing technology through horizontal printing and vertical printing manners, respectively. Quasi-static axial compression tests were conducted to study the mechanical properties and energy absorption of the pyramidal lattice truss structures. These two types of printed lattice truss materials had close strength and rigidity. However, the vertically printed lattice truss structures had excellent ductility and their struts never broken off during compression. Three post failure styles of the vertically printed lattice truss structures were observed, including strain-hardening, stable deforming and softening and depending on the slenderness ratio of the strut. Theoretic analysis and finite element method (FEM) were performed to investigate the compression behaviors of the vertically printed lattice truss materials. Appropriate printing method and relative density could make the 3D printed pyramidal structures achieve excellent specific energy absorption.